Linear matrix inequalıty based robust control for multi degrees of freedom hybrid electromagnetic vibration isolation - Yalçın, Barış Can (My University, 2019)
Vibration isolation systems based on hybrid electromagnets, consisting of electromagnets and permanent magnets, have potential usage in many industrial fields, such as clean room design, stewart platform design, transportation, semiconductor manufacturing, suspension systems, and robotic surgery etc. due to providing mechanical contact free vibration isolation. Besides, a simple electromagnet has the ability of acting as if it is virtual spring or damping element. Using permanent magnets in the electromagnet structure has some crucial advantages, such as a minimized volume and a more compact structure. Furthermore, the necessary equalizer force for levitation can be generated by only the permanent magnet(s), which means, by using hybrid electromagnets, magnetic levitation can be achieved with considerably low energy consumption against different disturbance characteristics. This property is called zero-power behavior. However, the main problems of magnetic levitation process is that it has highly nonlinear nature. Even if it can be linearized, it has unstable pole(s), which makes the system vulnerable in terms of stability. In recent years, linear matrix inequality-based design of controllers has received considerable attention and become very popular due to their ability to satisfy multi-objective requirements. Yet, LMI based H2 state-feedback controllers, having gap, acceleration, current and voltage values in state-vector, for a 3-DoF vibration isolation stage having 4-pole hybrid electromagnets, have not been investigated so far. In the thesis, it has been studied whether there is a convex solution space for Lyapunov matrix inequalities to deal with multi-directional mechanic disturbances. LMI type of controller is structured to minimize the influence of both ground and direct disturbances varying at different magnitudes and frequencies on vibration isolation, zero-power, and protection of the levitation purposes. Moreover, the experimental setup used in this thesis has been designed to meet aforementioned purposes. The setup's design parameters of the experimental setup are explicitly given and the effectiveness of the proposed method is shown with the experimental results.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2019
Keywords: Zero-power; Pseudo-infinite stiffness; Magnetic levitation; Vibration isolation; Linear matrix inequalities